Geochemistry and contamination of sediments and water in rivers affected by the rupture of tailings dams (Brumadinho, Brazil) - Pacheco, Fernando António Leal; do Valle Junior, Renato Farias; de Melo Silva, Maytê Maria Abreu Pires; Tarlé Pissarra, Teresa Cristina [UNESP]; de Souza Rolim, Glauco [UNESP]; de Melo, Marília Carvalho; Valera, Carlos Alberto; Moura, João Paulo; Sanches Fernandes, Luís Filipe (Elsevier, 2023)
Understanding the geochemistry and contamination of rivers affected by the rupture of tailings dams is paramount to emergency water resources management. This needs the long-term monitoring of tailings, sediments and water along the river, and the understanding of how the tailings interact physically and geochemically with the natural sediments and flowing water. An effort of this kind is uncommon because of its cost and opportunity. The purpose of this study was to help filling this gap using the rupture of B1 tailings dam (Brumadinho, Minas Gerais, Brazil, 25 January 2019) as example. To accomplish the objective, 31 parameters of tailings, sediment and water were monitored weekly for three years after the event, spanning impacted and non-impacted sectors of Paraopeba River, including a dam reservoir that is attenuating the tailings propagation downstream. Using hierarchical clustering analysis, the parameters were assembled into groups. Associations between parameters within the groups pointed to processes and drivers controlling the concentrations of Fe, Mn, Al, As, Pb and P in water. The results suggested reductive dissolution of Pb- and Mn-bearing minerals in the impacted and dam reservoir sectors as key process. In the rainy period, dissolved Mn concentrations in the impacted sector raised exponentially with temperature increase; in the dam reservoir, they showed episodic peaks triggered by thermal stratification-related pH decreases. In general, total concentrations > dissolved concentrations indicating predominant particle transport. Besides, concentrations were higher for Fe, Al and Mn, in the rainy season, and in the impacted sector. In the dry season, stream flow-controlled sediment resuspension triggered desorption of Fe and Al from sand grains raising their dissolved concentrations. In the rainy season, a pH declining trend probably related with erosion of acid soils in the watershed caused gradual increases of Fe, Al and P, desorbed from clays and silts. The main conclusion is that the B1 dam rupture left a strong fingerprint in the concentrations of Fe and Mn in the river, especially in the rainy season, which lasts and keeps the use of Paraopeba River suspended.
Keywords: Desorption; Grain size; Mining-related river contamination; Reductive dissolution; Stream flow; Tailings dam rupture